Pengembangan dan Implementasi Sistem Kontrol Irigasi Tetes Otomatis Berbasis IoT untuk Lahan Pertanian Desa Oeltuah Kabupaten Kupang - Olivia de Haviland Basoeki; Yohanes S. Peli; Rochani Rochani; Yusak Mukkun; Otnial A. Mone; Johanis W.D. Therik; Imanuel Ch. Mauko; James J. Mauta; Agustinus Lau Tita; Heri Hardi; Syofi M. Lubis (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Limited air resources and inefficient irrigation practices are major challenges for agricultural management in dryland areas, such as in East Nusa Tenggara Province. Manual irrigation systems result in unmeasured air usage, uneven air distribution, and increased farmer workloads. Therefore, the implementation of efficient and adaptive irrigation technology to environmental conditions is necessary. This Community Service activity aims to implement an Internet of Things (IoT)-based automatic irrigation control system using the drip method on the agricultural land of a farmer group in Oeltuah Village, Taebenu District, Kupang Regency. The implementation method includes an initial survey, system design, device construction and installation, system testing, and mentoring for farmer partners. The developed system uses a soil moisture sensor, an ESP32 microcontroller, a Real-Time Clock (RTC) module, a water pump, and a drip irrigation pipe network connected to an internet-based monitoring system. The results of the activity show that the automatic irrigation system operates well and is able to increase the efficiency of air use and regulate watering schedules more consistently. With the support of ongoing mentoring, this technology has the potential to increase agricultural productivity and the development of smart agriculture models (smart farming) in dryland areas.